Hybrid decode-amplify and forward protocol of FD EH relaying network: outage probability analysis - Van-Duc Phan; Duy-Hung Ha; Minh Tran; Tran Thanh Trang; Thanh-Long Nguyen (Universitas Ahmad Dahlan, 2019)
Nowadays, many research papers focus on the WPCN problem and how to improve its efficiency. In this research, we propose and investigate Hybrid Decode-Amplify and Forward Protocol (HDAF) of the Full-Duplex (FD) Energy Harvesting (EH) Relaying Network with the Time Switching (TS) protocol. In the beginning stage, we present the HDAF mode, which can be work like a Decode-and-Amplify (DF) or Amplify-and-Forward (AF) modes based on the best of its performance in the FD EH relaying network. Furthermore, the closed-form expression of the outage probability (OT) is analyzed and derived in connection with the primary system parameters. Besides, the comparison of the system performance in the AF, DF, and HDAF is proposed and investigated. Finally, all the results are convinced by the Monte Carlo simulation for all cases.